2022
DOI: 10.1186/s12935-022-02500-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key serum biomarkers for the diagnosis and metastatic prediction of osteosarcoma by analysis of immune cell infiltration

Abstract: Background The role of circular RNAs (circRNAs) and microRNAs (miRNAs) in osteosarcoma (OS) development has not been fully elucidated. Further, the contribution of the immune response to OS progression is not well defined. However, it is known that circRNAs and miRNAs can serve as biomarkers for the diagnosis, prognosis, and therapy of many cancers. Thus, the aim of this study was to identify novel key serum biomarkers for the diagnosis and metastatic prediction of OS by analysis of immune cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 79 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…The TME plays a critical role in tumor growth and metastasis [4] . We have previously shown that TME-based key targets were signi cant indicators of tumor progression [29] . Alterations in the TME are mainly controlled by hypoxia, glycolysis, and altered extracellular acidity.…”
Section: Discussionmentioning
confidence: 99%
“…The TME plays a critical role in tumor growth and metastasis [4] . We have previously shown that TME-based key targets were signi cant indicators of tumor progression [29] . Alterations in the TME are mainly controlled by hypoxia, glycolysis, and altered extracellular acidity.…”
Section: Discussionmentioning
confidence: 99%
“…The expression profiles of circRNA in the body fluids between osteosarcoma patients and healthy people are different, 53 such as circRNAs in exosomes. Exosomal circRNAs can be taken up by neighboring or distant cells and influence physiological and pathological status of the recipient cells.…”
Section: Application Of Circrna In the Diagnosis And Treatment Of Ost...mentioning
confidence: 99%
“…Our research group has recently identified potential OS protein markers that can be found in blood from public databases (submitted manuscript). Also, potential circular RNAs and microRNAs have been identified in serum for the diagnosis and prediction of metastasis for OS [8]. In addition, a 7-mRNA signature has been found to be able to predict the prognosis of OS in pediatric patients [9].…”
Section: Osteopontin and Ccn3 Proteins Are Two Examples That Can Func...mentioning
confidence: 99%